Penerapan Prinsip Due Care Oleh Produsen Terhadap Peredaran Obat Di Masyarakat - Amtsal, Abdul; Pesulima, Theresia Louize; Balik, Agustina (PATTIMURA Law Study Review, 2025)
Due care principle or the principle of prudence is a principle that must be applied by producers in producing goods or services in order to ensure that the products produced are really safe for consumption. In addition, Article 8 of the Consumer Protection Law stipulates that business actors are prohibited from producing goods or products that are detrimental or even endanger others. However, in reality there are several pharmaceutical companies that produce syrup drugs that contain Harmful compounds and have already spread among the community causing great losses and threatening consumer lives. So, it is interesting to research from the perspective of applying the Due Care Principle to these problems. The purpose of this study is to find out and explain the application of the due care principle by manufacturers to the circulation of drugs in the community as well as the responsibility of manufacturers for syrup drugs containing harmful compounds. The research method used in this writing is a normative juridical research method with a legislative approach, a case approach and a conceptual approach, to answer the problems raised. The results of this study can be concluded that the application of the Due Care Principle by manufacturers to drug circulation in the community underlines the importance of manufacturers being more careful in maintaining quality and safety in producing and distributing drugs. This includes testing and surveillance, reporting and transparency, distribution chains, and vigilance against contamination of a drug product. And manufacturers who produce syrup drugs containing harmful compounds can be requested strict liability based on Article 19 of the Consumer Protection Law.